2007
DOI: 10.1002/lt.21277
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcus salivarius bacteremia and spontaneous bacterial peritonitis in liver transplantation candidates

Abstract: Bacterial infections are a serious complication of end-stage liver disease (ESLD) that occurs in 20% to 60% of patients. We retrospectively reviewed medical records of patients with ESLD who were identified by our microbiology laboratory as having Streptococcus salivarius bacteremia. Of 592 patients listed for transplantation between January 1998 and January 2006, 9 (1.5%) had 10 episodes of S salivarius bacteremia. Of 2 patients already receiving quinolone prophylaxis for spontaneous bacterial peritonitis (SB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 39 publications
1
8
0
2
Order By: Relevance
“…There are demographic similarities between the patients reported previously by Gautam et al 1 and the patients reported by Bert et al 2 in their letter to the editors in this issue of Liver Transplantation. We elected to concentrate on patients who presented with Streptococcus salivarius bacteremia after we had encountered a few such patients in our clinical practice.…”
Section: To the Editorssupporting
confidence: 74%
“…There are demographic similarities between the patients reported previously by Gautam et al 1 and the patients reported by Bert et al 2 in their letter to the editors in this issue of Liver Transplantation. We elected to concentrate on patients who presented with Streptococcus salivarius bacteremia after we had encountered a few such patients in our clinical practice.…”
Section: To the Editorssupporting
confidence: 74%
“…Coagulase-negative staphylococci, group B streptococci and viridans group streptococci (VGS) have also been detected in SBP (25,17,19). Despite reports of an increasing incidence of VGS-associated SBP (26), S. salivarius is detected in ascite culture from o1% (3/ 592) of patients with end-stage liver disease (27) and current studies identify VGS in 7% of patients with SBP (25). Although the applied multiplex PCR kit does not identify certain VGS (S. oralis, S. mitis, S. salivarius, S. gordonii and S. vestibularis), Aeromonas spp.…”
Section: Discussionmentioning
confidence: 99%
“…Among the members of the salivarius group, only S. salivarius is commonly identified from a variety of human infections (4,13,21). S. thermophilus has been isolated only from dairy products.…”
Section: Discussionmentioning
confidence: 99%